Fruit bats trade in the traditional markets of South Minahasa, North Sulawesi, Indonesia - TILTJE ANDRETHA RANSALELEH; MARTHA KAWATU; INDYAH WAHYUNI; JANE ONIBALA; MEIS JACINTA NANGOY; SINTYA UMBOH; UNSTAIN N. W. J. REMBET; SURYO SAPUTRO; SIGIT WIANTORO (Society for Indonesian Biodiversity, 2024)
Abstract. Ransaleleh TA, Kawatu M, Wahyuni I, Onibala J, Nangoy MJ, Umboh S, Rembet UNWJ, Saputro S, Wiantoro S. 2024. Fruit bats trade in the traditional markets of South Minahasa, Sulawesi, Indonesia. Biodiversitas 25: 716-725. The hunting and trading of fruit bats are significant sources of income for several communities in North Sulawesi, Indonesia. Therefore, this research aimed to map the market locations and identify the species of traded bats, along with their conservation status in South Minahasa District. Surveys of markets, hunters, and sellers were conducted for 5 months from May to September 2023. Morphological examinations were carried out on the traded bats, focusing on several parameters such as body weight, morphometric and description of the morphological characters. We identified the traditional markets which sell fruit bats (family Pteropodidae), Acerodon celebensis and Pteropus alecto meat, namely Berdikari Tumpaan, 54 Amurang, 45 Langsot Tareran, Tenga, Pakuure, Ongkaw, Soko Raanan Baru, Motoling, Poigar, Poopo, Pinaesaan Tompaso Baru, and Pinasungkulan Modoinding. Furthermore, two markets, namely Pakuure and Pinaesaan Tompaso Baru, were identified selling the small fruit bats (family Pteropodidae), Cynopterus minutus, Dobsonia exoleta, Nyctimene cephalotes, Rousettus amplexicaudatus, and Thoopterus nigrescens. According to the International Union for Conservation of Nature (IUCN) Red List, A. celebensis and D. exoleta are endemic bat species in Sulawesi with a conservation status of vulnerable and least concern, respectively. Fostering education and advocacy program is crucial to promote awareness and conservation strategy, especially for the 12 traditional markets which trade seven fruit bat species in South Minahasa, Sulawesi.